2023
DOI: 10.1038/s41419-023-05952-4
|View full text |Cite
|
Sign up to set email alerts
|

PDHA1 hyperacetylation-mediated lactate overproduction promotes sepsis-induced acute kidney injury via Fis1 lactylation

Abstract: The increase of lactate is an independent risk factor for patients with sepsis-induced acute kidney injury (SAKI). However, whether elevated lactate directly promotes SAKI and its mechanism remain unclear. Here we revealed that downregulation of the deacetylase Sirtuin 3 (SIRT3) mediated the hyperacetylation and inactivation of pyruvate dehydrogenase E1 component subunit alpha (PDHA1), resulting in lactate overproduction in renal tubular epithelial cells. We then found that the incidence of SAKI and renal repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 57 publications
(77 reference statements)
0
15
0
Order By: Relevance
“… 38 Previous studies have shown that cell cycle arrest and acetylation and lactylation modifications occur after injury in several models of AKI. 39 , 40 Clearly, these data showed that CDK12 knockdown in tubular cells could induce cellular injury through DNA damage and subsequently cause apoptosis and inhibition of proliferation.…”
Section: Discussionmentioning
confidence: 96%
“… 38 Previous studies have shown that cell cycle arrest and acetylation and lactylation modifications occur after injury in several models of AKI. 39 , 40 Clearly, these data showed that CDK12 knockdown in tubular cells could induce cellular injury through DNA damage and subsequently cause apoptosis and inhibition of proliferation.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, lactate is also implicated in lactylation processes ( 25 ). An et al discovered that hyperacetylation and subsequent inactivation of the pyruvate dehydrogenase E1 component subunit alpha (PDHA1) lead to an increase in lactate production, which in turn promotes the lactylation of the mitochondrial fission 1 protein (Fis1) and worsens the severity of S-AKI ( 28 ). Conversely, decreasing lactate levels and Fis1 lactylation can alleviate S-AKI ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…An et al discovered that hyperacetylation and subsequent inactivation of the pyruvate dehydrogenase E1 component subunit alpha (PDHA1) lead to an increase in lactate production, which in turn promotes the lactylation of the mitochondrial fission 1 protein (Fis1) and worsens the severity of S-AKI ( 28 ). Conversely, decreasing lactate levels and Fis1 lactylation can alleviate S-AKI ( 28 ). Additionally, our findings revealed a significant association between lactate and MAKE30 in sepsis patients, underscoring the importance of therapeutic interventions aimed at reducing blood lactate levels in septic patients.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed the mitochondrial homeostasis or dynamics was disrupted, as indicated by decreased mitochondrial membrane fluidity, the broken balance of fusion/fission, increased mitochondrial fragmentation in O-ADSCs. Previous study showed that excess mitochondrial fission may promote mitochondrial dysfunctions and lead to cell injury [ 53 , 54 ]. The data reveal that impaired mitochondrial morphology and structure lead to mitochondrial dysfunction, which leads to cell injury in O-ADSCs and ultimately to the reduction of cell activity.…”
Section: Discussionmentioning
confidence: 99%